Financial Market Volatility and Investor Behavior: Evidence from the Indonesian Stock Exchange - Rika Novyta Sari; Rajab Abdullah (Mustard Journal De Ecobusin, 2025)
This study investigates the relationship between financial market volatility and investor behavior in the Indonesian Stock Exchange, with a focus on behavioral dimensions such as sentiment, risk perception, overconfidence, and herding. Using survey data from active investors and quantitative modeling, the research identifies how psychological and social factors interact with market structures in shaping volatility. The findings reveal that behavioral elements explain more than half of the variation in investor perceptions of volatility, with sentiment and herding showing the strongest effects. These results suggest that market fluctuations in Indonesia are not merely the outcome of economic fundamentals but are significantly influenced by retail-driven trading patterns and the accelerating role of digital platforms. The study contributes to behavioral finance literature by demonstrating the contextual relevance of biases in an emerging market setting, where institutional stabilization is relatively weak and cultural factors magnify collective tendencies. Practically, the results underscore the importance of enhancing financial literacy, regulating digital market ecosystems, and promoting more sustainable investment strategies to mitigate destabilizing behaviors. The study also highlights the need for future research that integrates behavioral insights with macroeconomic and political variables to achieve a more comprehensive understanding of volatility in emerging economies.